(untitled) - Hohnson. Nkosi (Switzerland, 2004)
The epidemic affects the world of work in many ways: Discrimination against people with HIV threatens fundamental principles and rights at work, and undermines efforts for prevention and care; he disease cuts the supply of labour and reduces income for many workers; Valuable skills and experience are lost; Productivity falls in enterprises and in agriculture, and labour costs rise; Investment is undermined and tax revenue cut just as countries face more pressure on public services; The double burden on women gets heavier as they have to earn a livelihood and provide care to sick family members and neighbours.
Keywords: HIV Infections,United Nations,Health education,Nhiễm HIV,Liên Hiệp quốc,Giáo dục sức khoẻ; Prevention and control,Kiểm soát và phòng ngừa